Measurement of Atmospheric Refraction near the Horizon at Teluk Kemang - Zambri Zainuddin, Mohd; Ahmad, Nazhatulsbima (Malaysian Journal of Science, 2002)
Astronomical observations near the horizon have historically been measured for naval navigation and for determining the time of sunset. We had measured the variation of astronomical refraction near the horizon based on sun motion with an instrument called theodolite. We have collected several measurements of refraction from Telok Kemang, one of 26 sites for sighting young crescent in determining the month of Ramadhan, Syawal and Zulhijjah in Malaysia. Our measured values for refraction near the horizon is 35 arcminutes as compared to the standard value adopted 34 arcminutes.